2011
DOI: 10.1021/op200216y
|View full text |Cite
|
Sign up to set email alerts
|

Heat Pipe-Mediated Control of Fast and Highly Exothermal Reactions

Abstract: The synthesis of 1-ethyl-3-methylimidazolium ethyl-sulfate ([EMIM]EtSO 4 ) from 1-methyl-imidazole and diethyl sulfate suffers from highly exothermal behavior. Once the activation energy barrier is reached (E A = 89 kJ mol À1 ), the bimolecular reaction accelerates with a high reaction enthalpy (ΔH = À130 kJ mol À1 ). 1À3 The excess of heat has to be concurrently dissipated to avoid hot spots or thermal runaways. Depending on the volume flow velocity of the reactants and the applied reactor temperature, the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Since then, Löwe et al (2010) [54] have commented that the very fast thermal response times and passive heat transfer of the heat pipe can suppress thermal runaways, as any heat transfer fluctuations can be removed at a maximum velocity corresponding to sonic conditions, or a Mach number of 1 for the working fluid. Ehm and Löwe (2011) [77] also used the same heat pipe micro-reactor for ionic liquid synthesis. By rapidly increasing/decreasing the operating temperature in discrete steps, the authors demonstrated that the maximum temperature spike from the reaction could be shifted within the reactor.…”
Section: Rapid Temperature Management and Isothermalisationmentioning
confidence: 99%
“…Since then, Löwe et al (2010) [54] have commented that the very fast thermal response times and passive heat transfer of the heat pipe can suppress thermal runaways, as any heat transfer fluctuations can be removed at a maximum velocity corresponding to sonic conditions, or a Mach number of 1 for the working fluid. Ehm and Löwe (2011) [77] also used the same heat pipe micro-reactor for ionic liquid synthesis. By rapidly increasing/decreasing the operating temperature in discrete steps, the authors demonstrated that the maximum temperature spike from the reaction could be shifted within the reactor.…”
Section: Rapid Temperature Management and Isothermalisationmentioning
confidence: 99%
“…Towards this end, heat pipes were used for dynamic cooling of microstructured reactors by Löwe et al. in the synthesis of 1‐ethyl‐3‐methylimidazolium trifluoromethane sulfonate (Scheme ) 58. 59 With this reactor setup, the cooling rate could be automatically adjusted, depending on the released heat, thereby avoiding the formation of hot spots and thermal runaways.…”
Section: Making Use Of the “Forbidden”—ex‐regime/high Safety Procementioning
confidence: 99%
“… Flow synthesis of 1‐ethyl‐3‐methylimidazolium trifluoromethanesulfonate with heat‐pipe dynamic cooling 58…”
Section: Making Use Of the “Forbidden”—ex‐regime/high Safety Procementioning
confidence: 99%